MAPPING POTENTIAL FOR WIND ENERGY IN COASTAL MARINE SENGGIGI FOR RENEWABLE ENERGY DEVELOPMENT SUPPORT - Muliadi -; Eliza Ruwaidah; Akhmad Asyari (Master in Systems Engineering, 2015)
His form of energy self-sufficient villages throughout Indonesia is the government's goal in the field of energy. Utilization of wind energy as a renewable energy source is an attempt to answer the problem for change and the natural environment is also one of the conservation of conventional energy sources. The purpose of this research study is to get the wind potential in accordance with the site characteristics such as speed and direction as a basis for planning SKEA. Potential awakened power of the wind potential and value of the benefits to be derived based on economic analysis if the potential energy is utilized for the generation of renewable energy on the grid system. The method used is the method of distribution. The results of the analysis of wind energy potential in Selaparang in 2011 until 2013, increased in 2011 the potential energy of 278, 5 KW KW rose to 562.5 in 2012 and in 2013 to 522, 4 KW wind speed has increased so the potential for increased power. Increased wind speed at the beginning of the year and the end of the rainy season occurred. The magnitude of the potential of wind energy can be used for supplying the electricity needs of the population about the number of households 500. The potential of wind energy in Kediri in 2011 until 2013, the image can be seen that the energy per year decline in 2011 the potential energy of 1751.33 KW dropped to 636 , 96 KW in 2012 and declined in 2013 to 44.954 KW wind speed so that the lower the potential for wind power down. Economic analysis produces BCR value of 1.4. Wind speed in Kediri greater than in Senggigi same year, but increased wind speeds in Senggigi and in Kediri decreased.